Domestic patenting systems and foreign licensing choices - Tsai, Yingyi; Mukherjee, Arijit (Springer Verlag, 2017)
This paper examines a foreign technology holder’s licensing choices between royalty and fixed-fee scheme. We emphasize that foreign licensor chooses the quality of licensed technology when the licensee country does not implement perfect intellectual property protection for licensor’s technology. We study quality choice as the foreign licensor’s selection for a particular grade of technical skills. We show that fixed fee emerges as the equilibrium licensing scheme when both the transfer of his technology is relatively efficient and the licensee is sufficiently cost competitive in the domestic market, and that royalty licensing prevails otherwise. We further show it need not hold the general belief that welfare in the licensor country unambiguously rise with a stronger patenting system in the licensee country when, in particular, such patenting system in place is sufficiently lax.